2020
DOI: 10.34768/amcs-2020-0022
|View full text |Cite
|
Sign up to set email alerts
|

Flexible resampling for fuzzy data

Abstract: In this paper, a new methodology for simulating bootstrap samples of fuzzy numbers is proposed. Unlike the classical bootstrap, it allows enriching a resampling scheme with values from outside the initial sample. Although a secondary sample may contain results beyond members of the primary set, they are generated smartly so that the crucial characteristics of the original observations remain invariant. Two methods for generating bootstrap samples preserving the representation (i.e., the value and the ambiguity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…We will study the proposed transitivity properties in other real-world problems, e.g., to construct an equivalence measure that we may use in image processing. Moreover, in the future, we will also consider the possibility of using the transitivity and interval interpretation used in the work, taking into account the uncertainty in such interesting areas as the recommender systems (Rutkowski et al, 2019) or bootstrap methods (Grzegorzewski et al, 2020).…”
Section: B Pękala Et Almentioning
confidence: 99%
“…We will study the proposed transitivity properties in other real-world problems, e.g., to construct an equivalence measure that we may use in image processing. Moreover, in the future, we will also consider the possibility of using the transitivity and interval interpretation used in the work, taking into account the uncertainty in such interesting areas as the recommender systems (Rutkowski et al, 2019) or bootstrap methods (Grzegorzewski et al, 2020).…”
Section: B Pękala Et Almentioning
confidence: 99%
“…To avoid undesired repetitions which often appear in bootstrap Romaniuk and Hryniewicz [17][18][19] proposed a resampling method which enrich secondary samples with fuzzy observations imitating those from the primary sample but containing some incremental spreads on their 𝛼-cuts. Then Grzegorzewski et al [21,28] suggested another approach for generating bootstrap samples which may differ from the primary one but preserve the two-parameter canonical representation of each fuzzy observation, i.e., its value and ambiguity or the expected value and the width. We briefly discuss this method below, before introducing in Section 5 a new flexible bootstrap algorithm which preserves three-parameter canonical representation comprising the value, ambiguity and the fuzziness of a fuzzy number.…”
Section: Value-ambiguity (Va) Bootstrap Algorithmmentioning
confidence: 99%
“…where m denotes the size of the secondary sample (see also Ref. [28]), 𝜃 = 1 and 𝜆 stands for the Lebesgue measure.…”
Section: Standard Error Of the Estimatorsmentioning
confidence: 99%
“…Quantum computing is believed to be a source of new ideas and solutions leading to a very significant increase of computations performance, especially by shortening its duration in many areas of science e.g. applications to fuzzy logic [1], machine [2] and deep learning methods [3]. Unfortunately, quantum computers are still in an early stage of development what may be seen in restricted capabilities and an appearance of a high intensity of errors appearance during the computational process.…”
Section: Introductionmentioning
confidence: 99%
“…The utilised Python distribution is dedicated for Intel One API 2022.0.22 package. The numerical experiments were performed in virtual environment WSL2 for Windows 11 (version 10.0.22000.613), Linux kernel 5.10.102 1. The speedup values for different sizes of quantum system given by (112), where N is the number of qubits.…”
mentioning
confidence: 99%